Unlocking the agro-physiological potential of wheat rhizoplane fungi under low P conditions using a niche-conserved consortium approach - Benbrik, Brahim; Reid, Tessa E.; Nkir, Dounia; Chaouki, Hicham; Aallam, Yassine; Clark, Ian M.; Mauchline, Tim H.; Harris, Jim A.; Pawlett, Mark; Barakat, Abdellatif; Rchiad, Zineb; Bargaz, Adnane (Oxford University Press (OUP), 2025)
Plant growth-promoting fungi (PGPF) hold promise for enhancing crop yield. This study delves into the fungal diversity of the wheat rhizoplane across seven Moroccan agricultural regions, employing a niche-conserved strategy to construct fungal consortia (FC) exhibiting higher phosphorus (P) acquisition and plant growth promotion. This study combined culture-independent and culture-dependent methods exploring taxonomic and functional diversity in the rhizoplane of wheat plants obtained from 28 zones. Twenty fungal species from eight genera were isolated and confirmed through internal transcribed spacer (ITS) Sanger sequencing. P solubilization (PS) capacity was assessed for individual species, with Talaromyces sp. (F11) and Rhizopus arrhizus CMRC 585 (F12) exhibiting notable PS rates, potentially due to production of organic acids such as gluconic acid. PGPF traits and antagonism activities were considered when constructing 28 niche-conserved FC (using isolates from the same zone), seven intra-region FC (different zones within a region), and one inter-region FC. Under low P conditions, in planta inoculation with niche-conserved FC (notably FC14 and FC17) enhanced growth, physiological parameters, and P uptake of wheat, in both vegetative and reproductive stages. FC14 and FC17, composed of potent fungi such as F11 and F12, demonstrated superior plant growth benefits compared with intra- and inter-region constructed FC. Our study underscores the efficacy of the niche-conserved strategy in designing synthetic fungal community from isolates within the same niche, proving significant agro-physiological potential to enhance P uptake and plant growth of wheat.
Keywords: Fungal consortia; fungal diversity; niche-conserved; phosphate; plant growth promotion; rhizoplane; 30 Agricultural, Veterinary and Food Sciences; 31 Biological Sciences; 3107 Microbiology; 3108 Plant Biology; 3004 Crop and Pasture Production; 2 Zero Hunger; Plant Biology & Botany; 3101 Biochemistry and cell biology